Higienização de lodos de esgoto com resíduos alcalinos da indústria siderúrgica - Haddad, Hyasmin Holz (2022)
Cleaning the sludge from sewage treatment plants (ETE) is an important step in sludge management, as this process ensures low levels of pathogenicity in the sludge which, when disposed of in the soil, does not cause a negative impact on the health of the population and the environment. environment. CONAMA Resolution Nº 498/2020 establishes the minimum requirements for the stability process, which includes a series of physical, chemical or biological processes, being one of the main processes to stabilize alkaline (generally with lime). Given this scenario, this research aimed to demonstrate the feasibility of using steel slag (LD) and the dust bag filter in the sewage sludge bathroom. In this study, dewatering experiments of sludge removed from a UASB reactor, on a small scale, were initially performed using geotextiles to evaluate the natural dewatering kinetics of sludge used in the toilet process. Simultaneously, samples of lime and steel residues were characterized by compositional X-ray fluorescence analysis. subsequently, the amount of alkaline substance necessary for cleaning the sewage sludge was determined. In addition, the mixtures were maintained under leached and solubilized guarantee processes in accordance with ABNT NBR 10005 and ABNT 1006 standards. Through FRX analysis, a predominance of Ca components can be observed in all analyzed materials. Regarding the sanitation tests, the pH results in both experiments provide the conditions required by CONAMA Resolution Nº. 498 (2020) for the chemical stabilization process. Furthermore, it can be concluded that the ideal dose of alkaline material from this study is 30% in dry mass of sludge. In the experiments, the efficiency of removal of thermotolerant coliforms was greater than 99.99% and the average concentration of thermotolerant coliforms in the biosolid both produced was < 1.8x100 MPN/g.ST. Regarding the viable eggs of helminths, in all samples of sludge and biosolids produced there were < 0.25 Egg/g ST. Thus, it is clear that in all treatments, the microbiological parameters meet the concentrations recommended by Conama Resolution Nº 498 (CONAMA, 2020), for Class A biosolids and ABNT NBR 10,004, with regard to environmental classification.